Potret Pemamanan pada Akulturasi Budaya Alas dan Gayo - Harinawati Harinawati; Richa Meliza (Department of Anthropology, 2022)
Abtract: Pemamanan is a tradition of Alas Culture at the time of traditional wedding and circumcision processions, this tradition is carried out by pure Alas tribal families and families who experience Cultural Acculturation, the purpose of this study is to describe the portrait of pemamanan in Alas and Gayo Cultural Acculturation, this research map will look at the Procession Pemamanan in Alas and Gayo Cultural Acculturation in mixed marriages, the results of the study show that the Acculturation of Alas and Gayo Cultures is not carried out 100% following the transition of Pemamanan from the Alas Tribe, the tolerance of Alas Culture (Father) to Gayo Culture (Mother) in traditional processions, but did not completely eliminate the Pemamanan tradition. Based on the results of the study, it can be concluded that the Portrait of the Pemamanan Tradition in the Acculturation of the Alas and Gayo Cultures gave birth to cultural tolerance in the two tribes.Abstrak: Pemamanan merupakan sebuah tradisi Budaya Alas pada saat melakukan prosesi adat perkawinan maupun Khitan, tradisi ini dilakukan oleh keluarga pure suku Alas maupun keluarga yang mengalami Akulturasi Budaya, tujuan penelitian ini adalah mendeskripsikan potret pemamanan pada Akulturasi Budaya Alas dan Gayo, peta penelitian ini akan melihat Prosesi Pemamanan pada Akulturasi Budaya Alas dan Gayo pda perkawinan campuran, hasil penelitian menunjukan bahawa Akulturasi Budaya Alas dan Gayo Potret Pemamanan dilakukan tidak 100% mengikuti trasisi Pemamanan dari Suku Alas, adanya toleransi Budaya Alas (Bapak) terhadap Budaya Gayo (Ibu) pada prosesi adat, namun tidak menghilangkan sepenuhnya tradisi Pemamanan. Berdasarkan hasil penelitian, maka dapat disimpulkan Potret Tradisi Pemamanan Pada Akulturasi Budaya Alas dan Gayo melahirkan toleransi Budaya pada kedua suku tersebut.